Herb-drug interaction resources: The PHYDGI database - J. Perrot; C. Bennetau-Pelissero; G. Miremont-Salamé; F. Petitet; S. Cluzet; H. Peyrouzet; L. Letinier (Elsevier, 2022)
Background: According to the WHO, about 60% of the world's population currently uses traditional herbal remedies as complementary or alternative medicine and 80% of the population in developing countries depends almost totally on them for their primary health-care requirements. Due to a lack of knowledge on the action mechanisms of plant compounds or mixture, concerns regarding the safety of potential Herb-Drug Interactions (HDIs) have been raised. Over the past two decades and by 2018, 124 WHO Member States had implemented regulations on herbal medicines. However, databases of interactions between plants and modern allopathic drugs are still limited. Methods: This study aims to build a database containing the information required for the proper concomitant use of chemical drugs and plant remedies. To develop the HDI database, scientific research articles were searched online using Medline, Scopus and Google scholar databases. Specific key-words, including plant names and "herb" "drug" "interactions" were questioned. Articles were then selected on the availability of required information including the fine identification of the plant extracts. Peculiar attention was paid on data reliability, and redundancies in interaction data increased their credibility. To inform about this reliability, a specific grade was applied. Besides, a grade based on the strength of pharmacokinetic changes was also given. Results: As of February 2022, the PHYDGI database allows health care professionals, researchers and manufacturers of plant-based remedies and dietary supplements to search an entity amongst 58 plants and its potential interactions with a given drug amongst 114 commonly used medical substances. Conclusion: The PHYDGI database integrates scientific data on HDI in well-structured forms including reference to the scientific sources. It provides herbal entities and their interactions as well as the level of strength for the pharmacokinetic interactions. This database which will be available for health practitioners, for phyto-drugs and food supplement manufacturers should help reducing potential HDI and developing safe use of plant-based remedies or supplements.